Health Tourism and Grey Tourism: A Virgin Opportunity for Economical growth of Nepal - Dhungel, Kshitiz Upadhyay (Journal of Karnali Academy of Health Sciences, 2024)
Health tourism has emerged as a growing fashion worldwide in last few decades. It is driven by the longing to travel to other countries to improve/maintain their health while experiencing the indigenous, cultural and tourist attractions of destinations.